Proceedings of the 2021 7th Student Computer Science Research Conference (StuCoSReC) - Fister, Iztok; Brodnik, Andrej; Brest, Janez; Fister Jr., Iztok; Krnc, Matjaž; Zimic, Niko (2021)
The 7th Student Computer Science Research Conference is an answer to the fact that modern PhD and already Master level Computer Science programs foster early research activity among the students. The prime goal of the conference is to become a place for students to present their research work and hence further encourage students for an early research. Besides the conference also wants to establish an environment where students from different institutions meet, let know each other, exchange the ideas, and nonetheless make friends and research colleagues. At last but not least, the conference is also meant to be meeting place for students with senior researchers from institutions others than their own.
Keywords: student conference; computer and information science; artificial intelligence; data science; data mining